DAMPAK KONFLIK KASHMIR DALAM SEJARAH SOSIAL EKONOMI INDIA - Rohmah, Desi Nur; Wulandari, Nuryuana Dwi (Universitas Negeri Gorontalo, 2024)
South Asia consists of Afghanistan, Pakistan, India, the Maldives, Sri Lanka, Bhutan, and Nepal. These countries share a history of European colonization, similar climates, and close proximity. India is known as one of the oldest civilizations, while Pakistan is the largest Muslim-majority country with a diverse ethnic background. The researcher studies the conflict between India and Pakistan using a literature study method. The research examines the Kashmir conflict, which began with territorial disputes between Hindus and Muslims in India, developed into a prolonged conflict between India and Pakistan, and led to the creation of Bangladesh in 1971. The conclusion is that cultural and religious differences prompted the partition of India.